0

# What does the b in mx b stand for?

Updated: 12/20/2022

Wiki User

10y ago

Be notified when an answer is posted

Earn +20 pts
Q: What does the b in mx b stand for?
Submit
Still have questions?
Related questions

The y-intercept.

### What does b stand for in a equation of a line?

y=mx+b m is the slope, b is the y-intercept (where the line will cross the y axis.

### Example of a slope intercept form?

Slope intercept form is y=mx+b the m would stand for your slope and b would stand for you y intercept written as (0,b)

### Y equals mX plus b rearrange to solve for b?

y = mx + b y - mx = b

### In the standard equation for a line what does the variable B stand for?

If you mean the straight line equation of: y = mx+b then m is the slope and b is the y intercept

### Give examples of y equals mx plus b?

y=mx+b mx+b=y (mx means multipy.) Hope this helps! -natali4everca

### What does MX stand for in mx newspaper?

Melbourne Express

### Why is the letter m used to stand for slope like how y equals mx plus b?

It is an arbitrary convention.

### Is y equals mx plus b the same thing as y equals b plus mx or do you need to convert it?

same thing. but its easy to change y=b+mx to y=mx+b

b = y - mx.

### How do you change point-slope to slope-intercept?

Given the point P = (a, b) and slope m, the point-slope equation is(y - b) = m*(x - a)y - b = mx - may = mx - ma + bwhich can be re-written asy = mx + (b - ma) which is of the slope-intercept form y = mx + c in which c = b - ma.Given the point P = (a, b) and slope m, the point-slope equation is(y - b) = m*(x - a)y - b = mx - may = mx - ma + bwhich can be re-written asy = mx + (b - ma) which is of the slope-intercept form y = mx + c in which c = b - ma.Given the point P = (a, b) and slope m, the point-slope equation is(y - b) = m*(x - a)y - b = mx - may = mx - ma + bwhich can be re-written asy = mx + (b - ma) which is of the slope-intercept form y = mx + c in which c = b - ma.Given the point P = (a, b) and slope m, the point-slope equation is(y - b) = m*(x - a)y - b = mx - may = mx - ma + bwhich can be re-written asy = mx + (b - ma) which is of the slope-intercept form y = mx + c in which c = b - ma.

### How do you Solve the formula y equals mx plus b for M?

the answer is: (y-b)/x = m y = mx + b y - b = mx (y-b)/x = m